Effect of SAKTI Implementation and IKPA on Financial Report Quality with Internal Control as an Intervening Variable - Asep Nasrulloh; Alias Nabire (Journal GoodWill, 2024)
This study aims to examine the influence of the implementation of the Agency-Level Financial Application System (SAKTI) and Budget Implementation Performance Indicators (IKPA) on the quality of financial reports, with internal control systems as an intervening variable. The research was conducted at the Directorate General of Strengthening Competitiveness of Marine and Fisheries Products, Ministry of Marine Affairs and Fisheries of Indonesia. The research method used is quantitative with a survey approach. Data were obtained from questionnaires distributed to 80 respondents and analyzed using multiple linear regression. The results of the study indicate that the implementation of SAKTI and IKPA significantly affects the quality of financial reports. Additionally, internal control systems were proven to mediate the relationship between the implementation of SAKTI and IKPA with the quality of financial reports. These findings emphasize the importance of implementing integrated information technology and budget performance indicators, as well as effective internal control systems to enhance transparency and accountability in government financial management. This study is expected to provide practical contributions to improving financial systems in government agencies and serve as an academic reference in the development of studies related to public sector accounting.